Pengaruh Lingkungan Kerja, Gaya Kepemimpinan, dan Stress Kerja Terhadap Kinerja Karyawan PT. Sinar Eka Selaras - Rizky, Hafiz Muhammad; Lestari, Setyani Dwi (MES Management Journal, 2025)
This study aims to examine and analyze the influence of work environment, leadership style, and job stress on employee performance at PT. Sinar Eka Selaras. A quantitative approach was employed using a survey method and non-probability purposive sampling technique involving 110 respondents. Data were collected through a Likert-scale questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach with the assistance of SmartPLS software. The results show that the work environment significantly contributes to improving employee performance. Leadership style is proven to have a positive influence on employee performance. Job stress, however, does not show a significant effect on performance within this model. Collectively, work environment, leadership style, and job stress simultaneously explain 43.7% of the variance in employee performance, while the remaining 56.3% is influenced by other variables not examined in this study. Leadership style emerges as the most significant factor affecting performance. The work environment also shows a significant effect, although to a more moderate extent compared to leadership style. Job stress, in this study, does not have a direct significant impact on employee performance. These findings enrich the human resource management literature—particularly in the context of the public sector and retail technology—while providing a data-driven basis for corporate policy formulation.